Are Red Blood Cell Distribution Width and Platelet Count Useful for Diagnosing Periprosthetic Joint Infection in Patients Undergoing Re‐Revision Arthroplasty - Yangming Zhang; Qiyu Xie; Boyi Jiang; Wenyu Jiang; Hong Xu; Zongke Zhou (Orthopaedic Surgery)
Objective Accurate and prompt identification of periprosthetic joint infections (PJIs) is critical prior to re‐revision arthroplasty to ensure optimal surgical outcomes. Among routinely measured blood indices, red blood cell distribution width (RDW) and platelet count (PLT) have shown strong correlations with infection presence. This study aimed to assess the utility of RDW and PLT for diagnosing PJI in patients scheduled for re‐revision arthroplasty. Methods This retrospective research encompassed all patients who underwent re‐revision hip or knee arthroplasty at our institution from 2008 to 2022. Participants were categorized into either the PJI (n = 41) or the non‐PJI (n = 47) group following the guidelines established in the 2013 International Consensus Meeting on PJI. In this analysis, RDW and PLT counts were evaluated alongside conventional inflammatory markers, including C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR). The efficacy of these diagnostics was evaluated by the area under the receiver operating characteristic (ROC) curve ([area under the curve AUC]). Results RDW demonstrated a modest AUC of 0.678 with sensitivity at 61.0% and specificity at 71.7%, using a threshold of 14.5%. PLT was on par with ESR, showing an AUC of 0.773, and both sensitivity and specificity around 73% at a threshold of 201 × 109/L. CRP presented the highest diagnostic accuracy with an AUC of 0.815, achieving a sensitivity of 82.9% and specificity of 73.9% at a 6.9 mg/L threshold, surpassing ESR's AUC of 0.754. None of the biomarkers, individually or combined, outperformed CRP alone (p > 0.05). Conclusions In the context of re‐revision arthroplasty, RDW and PLT demonstrate limited efficacy as diagnostic biomarkers for PJI. However, CRP retains its reliability as a biomarker when the diagnostic threshold is appropriately recalibrated.